ECOPRENEURSHIP AS A SOLUTION TO ENVIRONMENTAL PROBLEMS: IMPLICATIONS FOR UNIVERSITY ENTREPRENEURSHIP EDUCATION - Masjud, Yunita Ismail (UI Scholars Hub, 2020)
Environmental degradation is a consequence of using resources for economic purposes only. The impact of entrepreneurial activity, especially as industry, deteriorates the environment. University-offered entrepreneurship programs produce entrepreneur that can solve unemployment and low-income problems. By extension, more entrepreneurs will increase business activity and increasingly degrade the environment. The aims of this research were to examine the intentions of university students to become entrepreneurs using personal attitude, subjective norms, and self-efficacy as the driving factors; find the social intention of university students to become entrepreneur using empathy, self-efficacy, and exposure as inspirations; and explain the role of entrepreneurship education can play in environmental sustainability. In this research, the sample was chosen using quantitative methods from a population of President University, Faculty of Business students, Cikarang, West Java. The data collection method was a survey using a questionnaire, assessed by multiple regression data analysis. The results showed that entrepreneurial intention was significantly influenced by personal attitude, subjective norms, self-efficacy, and socioentrepreneurial intention. Internal factors significantly influenced students’ ambitions to become entrepreneurs. In term of environmental sustainability, entrepreneurship education was needed to implement ecopreneurship approach.